PENDIDIKAN DAMAI MELALUI PENDIDIKAN AGAMA PADA SEKOLAH MENENGAH ATAS DI DAERAH PASCA KONFLIK (Studi di SMA St. Fransiskus Asisi Bengkayang dan SMA Shalom Bengkayang) - Nugroho Eko Atmanto (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
The purpose of education is to develop mutual respect, peace, and harmony. Education should be able to rebuild harmony and peace among its community members especially in conflict areas. This study examines the implementation of peace culture education through religious education in post-conflict area of Bengkayang district. It uses qualitative approach through interview, observation and document studies. The results show that the content of peace culture education has been delivered through religious education, namely Catholic and Christian religious education in accordance with its foundation background. The things that support the implementation of peace culture education are the curriculum content, school policy, and teacher competence. While the obstacles are a long history of conflict that is not easy to forget, the awareness of teacher on peace culture education and of people not to retell conflict and ethnic disgraces stories from generation to generation.